2017
DOI: 10.1016/j.adolescence.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The role of career adaptability and courage on life satisfaction in adolescence

Abstract: The present study aimed to extend understanding about the relationship between career adaptability, courage, and life satisfaction in a sample of Italian adolescents. It was hypothesized that courage partially mediated the relationship between career adaptability and life satisfaction. Specifically, 1202 Italian high school students with an age from 14 to 20 years (M = 16.87; SD = 1.47), of which 600 (49.9%) boys and 602 (50.1%) girls, were involved. Using a multigroup approach across gender, it was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
92
3
6

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(110 citation statements)
references
References 43 publications
9
92
3
6
Order By: Relevance
“…More specifically, the career-counseling services should implement their interventions toward two directions: 1) monitoring the degree of students’ satisfaction during their academic career because high levels of satisfaction prevent them from dropping out and are related with academic success; moreover, high levels of academic satisfaction contribute to a coherent career identity; 2) developing psychological resources, such as proactivity, 74 emotional intelligence, 75 , 76 resilience, 77 courage 78 , 79 and mindfulness, 80 – 82 readiness, career adaptability, 83 and career identity through specific career-counseling or career-education programs. These interventions could contribute to helping students, after completing their degree, become more aware of their resources and able to face the numerous future transitions.…”
Section: Conclusion and Limitationmentioning
confidence: 99%
“…More specifically, the career-counseling services should implement their interventions toward two directions: 1) monitoring the degree of students’ satisfaction during their academic career because high levels of satisfaction prevent them from dropping out and are related with academic success; moreover, high levels of academic satisfaction contribute to a coherent career identity; 2) developing psychological resources, such as proactivity, 74 emotional intelligence, 75 , 76 resilience, 77 courage 78 , 79 and mindfulness, 80 – 82 readiness, career adaptability, 83 and career identity through specific career-counseling or career-education programs. These interventions could contribute to helping students, after completing their degree, become more aware of their resources and able to face the numerous future transitions.…”
Section: Conclusion and Limitationmentioning
confidence: 99%
“…Sovet et al, 2018) or life satisfaction (e.g. Ginevra et al, 2017). For instance, the results of Ginevra et al's (2017) in a large sample of Italian high school students (N=1202) aged from 14 to 20 showed that courage partially mediated the relationship between career adaptability and life satisfaction in both boys and girls.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Career adaptability can also be reflected in increased career success as it is positively associated with managing work changes (Neuenschwander & Garrett, 2008;Germeijs & Verschueren, 2007), job performance, work engagement (Rudolph et al, 2017), career engagement (Nilforooshan & Salimi, 2016), employment status (Guan et al, 2013), and employment quality (Koen et al, 2012). Research has shown that with increasing career adaptability, perceived internal barriers and external barriers decrease, while the perceived quality of life and extent of interests (Soresi, Nota, & Ferrari, 2012), career satisfaction (Rudolph et al, 2017), job satisfaction (McKenna et al, 2016;Han & Rojewski, 2015;Tolentino, Garcia, Restubog, Bordia, & Tang, 2013), as well as life meaning (Buyukgoze-Kavas, Duffy, & Douglass, 2015) and life satisfaction (Ginevra et al, 2018;Hirschi, 2009) increase. In this perspective, highly developed career adaptability can make the school-to-work transition, and dealing with accidental or planned career changes, easier.…”
Section: Empirical Findings About Career Adaptabilitymentioning
confidence: 99%